Kajian Teknologi Budidaya Pada Domestikasi Tumbuhan Berkhasiat Obat “Ciplukan (Physalis angulata. l)”untuk Mendukung Pengembangan Tanaman Obat Keluarga (TOGA) dan Ekonomi Kreatif - Karwati Zawani (CROP AGRO, Scientific Journal of Agronomy, 2021)
Most of morel berry (Physalis angulata. L), to this date, are still obtained from wild herbs grown in the house yard, rice fields, or gardens (Widiyastuti, 2002). The continuous obtaining without cultivation is afraid to lead this plant into scarcity to extinction. Hence domistication of morel berry is considerably important to do as an effort to preservation and fulfilling the needs of morel berry both as a foodstuffs and medicinal ingredients. This research aimed to examine morel berry cultivation (Physalis angulata. L) in polybag and in field technology to preserve and support Family Medicinal Plant Development Program (TOGA) and sustainable creative economy. To achieve the aim, experimental research was done with 3 sub-topics, namely: 1). Study of plant spacing and distribution of various fertilizers for the growth and yield of morel berry (Physalis angulataL.). 2) The application of organic fertilizer to morel berry cultivation (Physalis angulata. L) in polybag 3). Study of morel berry (Physalis angulata l.) cultivation as insert plants in cultivated land of yardlong beans (Vigna sinensis. L). This research was done in three location, namely: in villagers grounds of Sedau Village Narmada District, in experimental field of Agriculture Faculty UNRAM in Nyiur Lembang Narmada, and in a rice field of a farmer in Ubung Village Central Lombok Regency. The result of research from these three subtopic experiment that has been done is as follows: (i) Plant spacing test and chicken manure, NPK, and Petroganik application has not significant to morel berry growth and yield. (ii) . Pomi fertilizer application on vermicompost media generated highly significant influence to fruit quantity and fruit weigh per plant based on the outcome. It is resulted in the outcome which highly increased up to 463%-843%. (iii) Yardlong bean cultivated land could be used as an alternative to develop or cultivate morel berry as intercropping plant, and also as additional outcome for yardlong bean farmer. Inserted morel berry in yardlong bean field which planted with 40 cm x 60 cm spacing, produced morel berry weighted 189 kg/ha and yardlong bean with thrice harvest produced fruit weighted 4,445 ton/ha